Evaluation of common in vitro used chemicals' effect on motility and chromatin stability of boar spermatozoa - TSAKMAKIDIS (Ι.Α. ΤΣΑΚΜΑΚΙΔΗΣ), I. A.; KHALIFA, T.; LYMBEROPOULOS (Α.Γ. ΛΥΜΠΕΡΟΠΟΥΛΟΣ), A. G.; MICHOS (Η.Α. ΜΙΧΟΣ), I. A.; BOSKOS (Κ.Μ. ΜΠΟΣΚΟΣ), C. M. (Journal of the Hellenic Veterinary Medical Society, 2017)
Chemicals such as heparin, calcium ionophore and dimethyl sulfoxide (DMSO) have been used in sperm's function evaluation assays, since they are facilitating the sperm capacitation and the induction of acrosome reaction. Many researchers modified porcine in vitro protocols purposing the improvement and validation of in vitro assays. The modification of the above mentioned chemicals' concentration could have a detrimental effect on sperm characteristics, relative to normal sperm function and fertilizing ability. The present study aimed to investigate in vitro effect of various concentrations of, a) heparin (2, 4, 6, 8 and 10 μg/ml), b) calcium ionophore A23187 (10, 20, 30 μΜ) and c) DMSO (1, 2, 3 % v/v), that have been used in sperm evaluation techniques, on chromatin instability and total motility of boar spermatozoa. Eight boars were used as semen donors, providing 20 ejaculates. Acridine orange test and subjective evaluation of semen by a microscope equipped with a heated plate were performed in order to evaluate chromatin integrity and motility, respectively. The results of this study showed that the addition of heparin, A23187 and DMSO at concentrations of 8 - 10 μ^πιΐ, 10 μΜ and 1%, respectively, can be used for in vitro handling of boar spermatozoa without reduction of their motility and chromatin quality.